“I remember it...I feel it” Place’s Intangible Identity: Explorations through the Lens of Micro-phenomenology- Case Study of Al-Sultan Hassan Complex - Mohamed El Zoheiry, Sarah (AUC Knowledge Fountain, 2025)
In today’s contemporary architecture, the growing of anonymous and interchangeable spaces has diminished the distinctive character of the place, its individuality and experiential signification, fostering placelessness. This research argues that the framework of reconsidering place’s atmosphere offers a pathway to reconnect people with places through emotional, sensory, and embodied encounters. This research investigates the phenomenology of place, focusing on the atmosphere as an intangible identity that transcends physical attributes and engages people's senses and feelings. By exploring the Al-Sultan Hassan complex, the study deepens the understanding of the transcendental quality of the atmosphere, it’s unfolding over time, and it’s associated atmospheric spatial attributes through people’s narratives. Following a core questions: How do people experience the atmosphere of a place? How atmosphere unfolds overtime? How do different spatial attributes influence people's feelings and resonate in their memories? How are the atmospheric spatial attributes reshaped and redefined by people? Using micro-phenomenology as the primary methodology, this research delves into lived encounters to uncover how atmosphere and atmospheric attributes are perceived, remembered, and reshaped by individuals. It proposes a framework for understanding atmosphere through the fusion of lived, mental, and material dimensions of place, addressing themes of subjectivity, embodiment, and dwelling as major ones from the perspective of phenomenology of place. The findings contribute to the discourse on the atmosphere in architecture. It also provides a framework for thinking and designing from an embodied perspective that transcend the limitations of placelessness. This framework can be used by thinkers, architects, urban designers, and policymakers to rejuvenate places with intangible identities based on people lived encounters.